Recombination in Magnaporthe grisea - Zeigler, Robert S. (Annual Reviews, 1998)
The heterothallic ascomycete, Magnaporthe grisea, is the blast pathogen of rice and about 50 other grasses, and has potential for sexual and asexual reproduction. In most populations, data from mating type, fertility assays, and genotypic diversity strongly suggest that the pathogen is asexual. However, parasexual recombination cannot be ruled out. Chromosome length polymorphisms and translocations may prevent successful meiosis in most populations. Pathogens of millets and some grasses growing with rice appear to be largely genetically isolated, though some gene flow may occur. Sexual fertility has repeatedly been reported in rice pathogens from mountainous regions of South and East Asia. Several means by which sexual fertility may be lost in an agricultural setting are advanced.